English as a lingua franca: Facts, benefits and costs. (6th April 2018) - Melitz, Jacques
Abstract: How much further can we expect the spread of English to go? What are the gains? What are the costs? The paper first tries to identify the areas of life where English already serves as a lingua franca in the world and those where the language faces sharp competition. The discussion goes on to show that the future advance of English will depend heavily on the motives to learn the other major languages in the world as well. The cultural market is the single one where the extraordinary progress of English threatens to go too far.